2(x-1)+3+-2x=7

Simple and best practice solution for 2(x-1)+3+-2x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-1)+3+-2x=7 equation:


Simplifying
2(x + -1) + 3 + -2x = 7

Reorder the terms:
2(-1 + x) + 3 + -2x = 7
(-1 * 2 + x * 2) + 3 + -2x = 7
(-2 + 2x) + 3 + -2x = 7

Reorder the terms:
-2 + 3 + 2x + -2x = 7

Combine like terms: -2 + 3 = 1
1 + 2x + -2x = 7

Combine like terms: 2x + -2x = 0
1 + 0 = 7
1 = 7

Solving
1 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| showthat:sin(pi/4+4x)=sin(pi/3-2x) | | 1.00+3.00=3.00+2.00 | | x=r+4+4r-2 | | 2y-8=5x | | M^2-11=38 | | 0.5m=0.76 | | 15/72X9/45 | | 1l+854l-44k=365 | | 1x-12=-5 | | -12=-11+n/-12 | | 6x^6/x^2 | | 1/4x+3=2 | | n^2-n-1520=0 | | 2v+5=29 | | 6=2p+8 | | 15-12(-7x-6)= | | 30=-10+4m | | 12/3*9+20=x | | (t+6)(t-6)=(t+7)(t-8)+9 | | 12/3=x | | -3/8m+1+-13/8m=5 | | 2/5(4y+2x) | | 10-82/3 | | -185=-5-9b | | 10-8/3 | | 2=6+k/4 | | 2x^4-5x^3-16x+40=0 | | 2x-(7/6)+(x/6)=(4x+3/6) | | 2x-(7/6)+(x/6)=(4x+3)/(6) | | 3h=0.12 | | 9e+10= | | 100e+10= |

Equations solver categories